Reconstruction of Issue Management and Political Communication Messages: An Islamic Perspective in the Digital Era - Muhammad Dalim; Hasrat Efendi Samosir (Walidem Institute and Publishing, 2026)
Objective: This study aims to reconstruct issue management and political communication messages from an Islamic perspective to address the ethical challenges of political communication in the digital era. Theoretical Framework: The study integrates Issue Management Theory, Political Communication Theory, and Islamic Communication Ethics, emphasizing the principles of ṣidq (honesty), amanah (responsibility), tabayyun (information verification), syūrā (deliberation), and maslahah (public benefit) as foundations for ethical political communication. Literature Review: Previous studies show that issue management issue management in digital political communication and islamic perspective on political communication messages. Method: This study employed a qualitative approach using library research. Data were collected from books, peer-reviewed journal articles, and relevant policy documents on issue management, political communication, digital media, and Islamic communication. The data were analyzed using content and thematic analysis to identify conceptual relationships and develop an integrative framework. Results: The findings indicate that issue management is essential for identifying political issues, preventing communication crises, and maintaining public trust. However, digital political communication is increasingly challenged by disinformation, political polarization, hate speech, and algorithm-driven information manipulation. Integrating Islamic communication ethics with issue management provides a normative and strategic framework for developing political messages that are transparent, accountable, and oriented toward public benefit. Implications: The proposed framework offers guidance for policymakers and political institutions in strengthening ethical digital governance and improving the quality of democratic communication. Novelty: This study introduces an Islamic Ethical Digital Issue Management Framework that integrates issue management with Islamic communication ethics, providing a new conceptual model for ethical political communication in the digital era.